Avaliação de Características de Crescimento Pós-Desmama de Animais Nelore Puros e Cruzados no Estado do Mato Grosso do Sul - De Souza Dantas Muniz, Carolina Amália [UNESP]; De Queiroz, Sandra Aidar [UNESP] (My University, 1999)
With the objetive to compare the genetic group performances for growth traits, data on 2888 yearling weight (YW) and average daily gain from weaning to yearling (AGY) and 1909 long yearling weight (LYW) and average daily gain from 365 day weight to 550 day weight (AGL), from progenies of Nellore cows mated to Aberdeen Angus, (red and black) Brangus, Gelbvieh, Nellore and Simmental sires in the State of Mato do Grosso do Sul were analyzed. The F1 genetic groups were: 1/2 Nellore + 1/2 Angus (1AG1NL), 1/2 Brangus + 1/2 Nellore (1BB1NL), 1/2 Red Brangus + 1/2 Nellore (1RB1NL), 1/2 Canchim + 1/2 Nellore (1CN1NL), 1/2 Gelbvieh + 1/2 Nellore (1GL1NL), 1/2 Simental + 1/2 Nellore (1SM1NL) and Nellore. Data were processed by least squares method using a mathematical model that included the fixed effects of contemporary groups (CG), genetic group (GG), age of calf and age of cow at calving. Contemporary Group and Genetic Group showed significant effects on all studied traits. Age of cow at calving was a significant source of variation on AGL, showing linear and quadratic effects. The crossbred animals were 25.9 kg and 34.8 kg heavier than the Nellore to YW and LYW, respectively. AGY and AGL were 67 and 21 g greater for crossbred than for Nellore, respectively. The F1 animals from groups 1AG1NL, 1GL1NL and 1SM1NL were 8% higher than Nellore for the studied traits. Among crossbreed, 1GL1NL and 1SM1NL tended to be higher for YW. Among the groups originated from sinthetic breeds, 1BA1NL, 1BV1NL and 1CN1NL, the crossbred group Canchim was 4 to 7% higher for all the traits analysed.
Post-Weaning Traits Evaluation of Straightbred and Crossbred Nellore Cattle in Mato Grosso do Sul State
Keywords: Average daily gain; Beef catlle; Crossbreding; Long yearling weight; Yearling weight